Health benefits of polyphenols: A concise review. Issue 10 (13th June 2022) - Rana, Ananya; Samtiya, Mrinal; Dhewa, Tejpal; Mishra, Vijendra; Aluko, Rotimi E.
Abstract: Plants produce polyphenols, which are considered highly essential functional foods in our diet. They are classified into several groups according to their diverse chemical structures. Flavanoids, lignans, stilbenes, and phenolic acids are the four main families of polyphenols. Several in vivo and in vitro research have been conducted so far to evaluate their health consequences. Polyphenols serve a vital function in the protection of the organism from external stimuli and in eliminating reactive oxygen species (ROS), which are instigators of several illnesses. Polyphenols are present in tea, chocolate, fruits, and vegetables with the potential to positively influence human health. For instance, cocoa flavan‐3‐ols have been associated with a decreased risk of myocardial infarction, stroke, and diabetes. Polyphenols in the diet also help to improve lipid profiles, blood pressure, insulin resistance, and systemic inflammation. Quercetin, a flavonoid, and resveratrol, a stilbene, have been linked to improved cardiovascular health. Dietary polyphenols potential to elicit therapeutic effects might be attributed, at least in part, to a bidirectional association with the gut microbiome. This is because polyphenols are known to affect the gut microbiome composition in ways that lead to better human health. Specifically, the gut microbiome converts polyphenols into bioactive compounds that have therapeutic effects. In this review, the antioxidant, cytotoxicity, anti‐inflammatory, antihypertensive, and anti‐diabetic actions of polyphenols are described based on findings from in vivo and in vitro experimental trials. Practical applications: The non‐communicable diseases (NCDs) burden has been increasing worldwide due to the sedentary lifestyle and several other factors such as smoking, junk food, etc. Scientific literature evidence supports the use of plant‐based food polyphenols as therapeutic agents that could help to alleviate NCD's burden. Thus, consuming polyphenolic compounds from natural sources could be an effective solution to mitigate NCDs concerns. It is also discussed how natural antioxidants from medicinal plants might help prevent or repair damage caused by free radicals, such as oxidative stress. Abstract : A brief overview of beneficial effects of polyphenols and its roles in human health.